2019
DOI: 10.1186/s13287-019-1318-6
|View full text |Cite
|
Sign up to set email alerts
|

High-content screen in human pluripotent cells identifies miRNA-regulated pathways controlling pluripotency and differentiation

Abstract: Background By post-transcriptionally regulating multiple target transcripts, microRNAs (miRNAs or miR) play important biological functions. H1 embryonic stem cells (hESCs) and NTera-2 embryonal carcinoma cells (ECCs) are two of the most widely used human pluripotent model cell lines, sharing several characteristics, including the expression of miRNAs associated to the pluripotent state or with differentiation. However, how each of these miRNAs functionally impacts the biological properties of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…miRNA from the first cluster (miR‐378a, miR‐143, miR 125a), strongly expressed in the mammalian heart, and largely involved in muscle development and hypertrophy, [ 52 , 53 , 54 , 55 , 56 ] were downregulated in hiPSC‐EV and gradually upregulated along cardiomyocyte differentiation (with exception of miR‐378a, which is also expressed in hiPSC‐EV). The second miRNA cluster (miR‐200b/c, miR‐335, miR‐302b/c, miR‐363, miR‐183, miR‐182), contained pluripotency‐associated miRNAs, [ 31 , 32 , 33 , 57 ] which were progressively downregulated in EV secreted from committed and mature cells. The third cluster is composed solely of two miRNAs (miR‐483, miR‐375), involved in lineage specification, which explains their absence in hiPSC‐EV and CMm‐EV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNA from the first cluster (miR‐378a, miR‐143, miR 125a), strongly expressed in the mammalian heart, and largely involved in muscle development and hypertrophy, [ 52 , 53 , 54 , 55 , 56 ] were downregulated in hiPSC‐EV and gradually upregulated along cardiomyocyte differentiation (with exception of miR‐378a, which is also expressed in hiPSC‐EV). The second miRNA cluster (miR‐200b/c, miR‐335, miR‐302b/c, miR‐363, miR‐183, miR‐182), contained pluripotency‐associated miRNAs, [ 31 , 32 , 33 , 57 ] which were progressively downregulated in EV secreted from committed and mature cells. The third cluster is composed solely of two miRNAs (miR‐483, miR‐375), involved in lineage specification, which explains their absence in hiPSC‐EV and CMm‐EV.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] Not all miRNAs are ubiquitously expressed, with tissue‐specific subsets, [ 20 ] such as myomiRs (miR‐1, miR‐133a, miR‐133b, miR‐206, miR‐208a, miR‐208b, miR‐486, and miR‐499), exclusively or preferentially expressed in striated muscle, [ 21 , 22 , 23 , 24 , 25 ] and involved in muscle cell proliferation and/or differentiation, or angiomiRs (miR‐126, miR‐130a, let‐7f, and the miR‐17‐92 cluster), expressed in endothelial cells and identified as key regulators in angiogenic processes. [ 26 , 27 , 28 , 29 , 30 ] Similarly, miRNA clusters were shown to be essential in stem cell maintenance (miR‐106a‐363, [ 31 ] miR‐302a‐367, [ 32 , 33 ] miR‐17‐92, [ 31 ] and C19MC clusters, [ 34 ] and miR‐200c/b) [ 35 , 36 ] and differentiation. [ 31 , 37 ] In fact, combinations of miRNAs were capable of inducing direct cellular reprogramming (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Archetypes of pertinent signalling pathways that might prove pivotal for crisis transition were selected for expression analysis (Figure 6 ). Of these, only the expression patterns of WIF1 ( 62 ) and DTX1 ( 63 , 64 ) (regulators of Wnt and Notch signalling, respectively) were reproduced by RT-PCR assays, both demonstrating increased mRNA levels in the transformed fibroblasts at the late crisis stage that, importantly, were manifestly higher than those measured in the Early (proliferating) and Late (senescent) NEO control fibroblasts ( Supplementary Figure S1A ). By RT-PCR, WIF1 was 3.5-fold increased ( P <0.0001) between early- and late-crisis E6E7 cells (compared with 99.5-fold by RNA-seq; P = NS) and 5.24-fold ( P < 0.0001) upregulated in the late-stage E6E7 compared with the NEO cells.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that miR-363-3p is associated with cell differentiation. For example, miR-363-3p promotes pluripotency maintenance through repression of NOTCH1 and PSEN1 and suppression of Notch-induced differentiation of human pluripotent cells [26]. Dendritic cells from peripheral blood of patients with rheumatoid arthritis promote Th17 cell differentiation through the miR-363-3p-integrin av-TGF-b axis [27].…”
Section: Discussionmentioning
confidence: 99%